Development of Causal Relationship Model of Learning Behavior via Internet of Lower Secondary Students in Bangkok Metropolis - Punnee Leekitchwatana (My University, 2013)
At present, internet is global information level that plays a very important role increasingly. It’s useful more or less depends on internet user behavior. Lower secondary school students are a group of people who close to and have most opportunity to use internet. Therefore, to study and understand their behaviors and causes of learning behavior via internet of lower secondary school students will be useful together with explain the cause of their behaviors. For that reason, this research has objective to study behavior and develop the causal relationship model of learning behavior via internet of lower secondary school students by selecting the causal relationship model of structural equation with latent variables. The independent variables included both of external and internal of student together. Data collection was conducted with 1,500 lower secondary school students in Bangkok Metropolis in academic year of 2011. The used questionnaire was 6 rating scales that composed of 128 items covering 20 observed variables. It had construct validity and construct reliability of 7 latent variables at good criteria. Statistics analysis was mean, standard deviation and SEM by LISREL program. The results illustrated as the followings. 1. Students had learning behavior via internet as whole at moderate level in every group both whole and sub-group classified according to sex and educational area into 5 sub-groups of male group, female group, Bangkok Metropolis area 1, area 2 and area 3. 2. The developed causal relationship had validity at good criteria for every model. The whole causal variables were able to predict the variation of result variable of behavior with 73.30% at whole group and between 50.10-85.10% in sub-groups. The causal latent variables of behavior had 6 variables, the order of influent values were family with 0.68, ability with 0.23, school with 0.20, affection with 0.14, friend with 0.07 and teacher with 0.03 respectively. DOI: 10.5901/mjss.2013.v4n4p39
Keywords: LISREL; Causal model; Online and Blended Learning